2017
DOI: 10.5603/gp.a2017.0107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of topical silicone gel and corticosteroid cream on the pfannenstiel scar prevention — a randomized controlled trial

Abstract: Objectives: To compare the effects of topical silicone gel and corticosteroid cream for preventing hypertrophic scar and keloid formation following Pfannenstiel incisions. Material and methods:Fifty patients operated for benign gynecological diseases through primary Pfannenstiel incision were included. The wounds were randomly allocated to the treatment and control arms. In the treatment arm, the wounds were divided into two halves; one was treated with silicone gel and the other with methylprednisolone cream.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…Existem também os tratamentos não invasivos, sendo os preferíveis para início do tratamento (MESECI et al, 2017). Dessa maneira, MESECI et al (2017) desenvolveu um estudo clínico para comparar a eficácia do gel de silicone e corticosteroide na prevenção de queloide em incisões de Pfannnestiel.…”
Section: Resultsunclassified
“…Existem também os tratamentos não invasivos, sendo os preferíveis para início do tratamento (MESECI et al, 2017). Dessa maneira, MESECI et al (2017) desenvolveu um estudo clínico para comparar a eficácia do gel de silicone e corticosteroide na prevenção de queloide em incisões de Pfannnestiel.…”
Section: Resultsunclassified
“…In addition, five RCTs using VSS did not report results in the form of mean ± standard deviation and were excluded . Finally, six RCTs with a total of 375 patients were included (Figure ). The baseline characteristics of the six studies were shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…If oral ACEI/ARB antihypertensive drugs are used in scar patients without hypertension solely to reduce scarring, they may cause undesirable side effects, such as hypotension. What is more, non‐invasive, painless and convenient treatments often enhance patient compliance 22 . So, if they can be used topically, the side effects of oral administration can be greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, non-invasive, painless and convenient treatments often enhance patient compliance. 22 So, if they can be used topically, the side effects of oral administration can be greatly reduced. To this end, our previous work explored and proved that the ACE participating in scar formation was derived from both bone marrow and local skin tissue, 23 indicating that inhabiting any one of the two ACE sources could probably be beneficial.…”
Section: Patient Itemsmentioning
confidence: 99%